EFFECTIVENESS OF WASTE MANAGEMENT WITH THE METHOD OF WASTE MANAGEMENT PLACE REDUCE, REUSE, RECYCLE - Soga, Sukmawan; Abdussamad, Juriko; Tui, Fenti Prihatini D. (Public Policy Journal, 2024)
This study aims to determine how effective waste management is based on the 3R Waste Management Site in Bone Bolango Regency. This study used a qualitative descriptive approach method, while the data collection techniques used were observation, interviews, and documentation. Based on the results of the study, it is known that the effectiveness of waste management based on the 3R Waste Management Site in Bone Bolango Regency includes, program success, target success, satisfaction with the program, suitability of inputs and outputs, overall goal achievement has gone quite well, but has not been effective. This was influenced by several obstacles such as problems procuring funds for operational costs, limited knowledge of human resources, and lack of attention and supervision from the government on 3R Waste Management Sites, causing several 3R Waste Management Sites to stop operating. Factors that determine the success of waste management based on the 3R Waste Management Site in Bone Bolango Regency include organizational characteristics, environmental characteristics, worker characteristics, and management practices. Overall, these factors have been carried out well, it can be seen from the existence of administrators or managers who run the 3R Waste Management Site, adequate internal and external environments, managers who are skilled and responsible in carrying out their duties, and the active role of the chairman in mobilizing their members.